Convergence of collaborative behavior in virtual teams: The role of external crises and implications for performance - Blay, Tobias; Froese, Fabian Jintae; Taras, Vasyl; Gunkel, Marjaana (Journal of applied psychology, 2024)
Organizations have increasingly relied on virtual teams (VTs). For VTs to succeed, the collaborative behavior of team members plays an important role. Drawing from the open systems theory and using a phenomenon-driven approach, we investigate the dynamic pattern of collaborative behavior convergence among members of VTs (i.e., the emergence of collaborative behavior consensus) and its relationship with VT performance. Moreover, we investigate the differential influence of external crises, exemplified by key dynamic facets of the COVID-19 crisis (i.e., COVID-19 health threat and social distance). We used a multilevel approach (i.e., time, individual, and team levels) with the multilevel group-process framework to test our hypotheses. Results from a survey of 3,506 participants nested in 703 teams suggest that collaborative behaviors of VT members tend to converge over time, leading to the emergence of collaborative behavior consensus. Furthermore, a dynamic COVID-19 health threat leads to lower collaborative behavior consensus over time. Moreover, our results show that collaborative behavior consensus is partially positively related to VT performance and is particularly important for VTs with a lower level of collaborative behavior at the end of the collaboration. The practical and theoretical implications of these findings are discussed. (PsycInfo Database Record (c) 2024 APA, all rights reserved).